Review on the Parameters Affecting the Relative Fiber-Matrix Stiffness of Fiber-Reinforced Concrete (FRC) - Mohd Shaharin, Arif Iskandar; Majid, Masni (Recent Trends in Civil Engineering and Built Environment, 2021)
Fiber-reinforced concrete (FRC) is an innovation that has been gaining interest by many researchers and those affiliated with the construction industry regarding ways on how to improve the strength of conventional concrete to sustain loads over time. Fiber-reinforced concrete is defined as concrete that contains fibers which can boost the tensile strength of the structure. Steel fibers, synthetic fibers, glass fibers, and natural fibers are some of the most well-known fibres, and each type of fibre imparts different qualities to concrete. Furthermore, different type of concretes, fibre types, geometries, densities, distribution and orientation of the fibers affect the properties of fiber-reinforced concrete. Despite the different type of materials of fiber, there are five types which is differentiate by its physical features such as hooked-end fibers, flat-crimped fibers, flat-end fibers, round-crimped fibers and double-anchored fibers. The problem that is issued is the parameters that can either increase or not in increasing the structural strength of fiber-reinforced concrete. The goal of this research is to study into the elements that influence fiber-reinforced concrete, as well as the variables that determine one of those aspects, relative fiber-matrix stiffness. About 28 previous research papers were reviewed and analyzed. All the reviewed papers regarding each factor and parameter are listed in references. All the papers were listed out in Table. It was found that the hooked-end type of fibers has the highest strength when being studied in each parameter with toughness of 210 Nmm.